2014
DOI: 10.5614/j.math.fund.sci.2014.46.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polymer Electrolyte Membrane based on Acid-Base Complex Pair and Its Characteristics

Abstract: Abstract. In this work, acid-base complex pair polymer electrolyte membranes on sulfonated polysulfone with 1H-benzotriazole were investigated. Polysulfone was sulfonated in 1,2-dichloroethane using the homogeneous method with trimethylsilyl chlorosulfonate as sulfonating agent. The monomer mole ratio between polysulfone and trimethysilyl chlorosulfonate was 1:1.5. The sulfonated polysulfone was added with 1H-benzotriazole at mole ratios of x = 0.5 and x =1. The proton transfer from 1H-benzotriazole to the sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This change in the trend in conductivity was attributed to the formation of an electric double layer . By extrapolating the plateau regions observed in Figure to a frequency of zero, the dc conductivities of the samples can be estimated, and those values are listed in Table . It is also clear from Figure that all complexes and HL follow the power law, σ ac = A ω s , where A is a temperature‐dependent constant, and s is the frequency exponent, which is a measure of the degree of interaction between the charge carriers and the environment .…”
Section: Resultsmentioning
confidence: 99%
“…This change in the trend in conductivity was attributed to the formation of an electric double layer . By extrapolating the plateau regions observed in Figure to a frequency of zero, the dc conductivities of the samples can be estimated, and those values are listed in Table . It is also clear from Figure that all complexes and HL follow the power law, σ ac = A ω s , where A is a temperature‐dependent constant, and s is the frequency exponent, which is a measure of the degree of interaction between the charge carriers and the environment .…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has been reported by previous studies. [15][16][17] is the peak stretching of O-H, where water is absorbed in the cavity and zeolite channel. While the peak at about 1635 cm -1 corresponds to the bending mode of O-H water.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] The sulfonation degree (DS) of polysulfone was measured by acid-base titrimetric method. The sulfonation ratio of sulfonated polysulfone was calculated as 187% ((mol SO3H/repeat unit) x 100).…”
Section: Preparationmentioning
confidence: 99%
“…Technol., 6(2), 52 -58 Agust 2017 doi: 10.13170/aijst.6.2.8438 Others research also have reported that the local wave number 3100 cm -1 also generated N ---H stretch, indicating the occurrence of protonation on the imidazole ring of poly benzimidazole as a result of the interaction between the hydrogen atoms on the sulfonate group (Oktay et al, 2009). Previous N ---H interaction on the polymer molecule has been reported synthesis of polymer electrolyte membrane based on acid-base complex pair (Gustian et al, 2014 b andGustian et al, 2016).…”
Section: Materials and Preparationmentioning
confidence: 99%